Fate and transport of surfactants in graywater when applied to soil - Huang, Zhaohua, author; Sharvelle, Sybil, advisor; Carlson, Kenneth, committee member; Stromberger, Mary, committee member (Colorado State University. Libraries, 2013)
Graywater reuse for irrigation has been considered an efficient way to reduce demand on water supply. Concerns, however exist regarding the potential impacts that graywater pose to soil quality. In particular, the fate of surfactants, the primary component in personal care and cleaning products, is not well understood. The objective for this study was to gain a better understanding of the adsorption behavior of surfactant onto soils, with particular attention on the effect of the organic matter and soil texture, then provide a suggestion about the kind of surfactants and soil be reused during graywater irrigation. Surfactants linear alkylbenzene sulfonates (LAS) (anionic), alcohol ethoxysulfates (AES) (anionic) and alcohol ethoxylates (AE) (nonionic) were applied to three different soils with varying organic matter (OM) and clay fraction column studies. Adsorption results were obtained from leachate and soil samples. The fraction ranges of leached surfactants to sorbed of LAS, AES and AE were 0.10-0.42, 0.42-2.35, 0.06-0.77 respectively. The results indicated that AES had the most potential leaching capacity, which mean they could reach deeper soil layer even groundwater systems. On the other hand, from soil properties, OM played an important role in the adsorption of surfactants, both anionics and nonionics, whereas, the clay fraction content had a negative effect on anionic surfactants sorption (p=0.006, 0.002 for LAS and AES), possibly due to an increase in negative charge, repulsion forces as clay content increasing, but not significant on nonionic surfactants with clay content increased from 33% - 46% (p=0.986 for AE). Meanwhile, AES homologues which contained different number of ethylene oxide (EO) groups were studied. Results indicated that adsorption increased as EO chain increased. Based on the results above, AE were recommended for graywater irrigation in terms of surfactants with relative high OM.
Keywords: AES; soils; LAS; graywater; adsorption; AE